The Qur'anic Vision Towards Minorities in a Plural Society: A Case Study in Kudus Regency, Indonesia - Fatah, Abdul; Imam Sadili; Arif Friyadi; Aufa Abdillah (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
This paper explores the Qura'nic vision of fostering harmony for minorities in a pluralistic society, using Karangrowo village in Kudus City, Indonesia, as a case study. Karangrowo, Kudus is a village with a long history of religious diversity and coexistence, where Muslims, Christians, and samin (local native faith) live together peacefully. The qualitative research method employed in this study involves collecting data related to the theme and conducting interviews with key informants considered to have expertise in the relevant topic. The paper analyzes the Qura'nic verses that promote tolerance, respect, dialogue, and cooperation among religious groups and how they are implemented in Kudus regency people's social and cultural practices. The paper also examines the challenges and opportunities for enhancing the Qura'nic vision of minority protection in the context of contemporary Indonesia, which faces various issues such as radicalism, extremism, and intolerance. The Qura'nic values of minorities are relevant and essential for creating harmony for minorities in a pluralistic society. Kudus can serve as a model and inspiration for other regions in Indonesia to create harmony and develop an inclusive society.